Sabbatical leave report. - Gregory, Jess L. (2019)
Sabbatical to write textbook: "School leadership for learning : learning theory to improve professional practice".
Keywords: dept.edl; faculty_collection; sabbatical_report

A quantitative exploration of students’ mindsets and behaviors: A whole child academic, emotional, and career development - Yavuz, Olcay (International Journal of Educational Reform, 2019)
The demands of the 21st century require a systemic and collaborative perspective to promote the long-term development and success of all children. The purpose of this international comparative study is to investigate students’ mindsets and behaviors for school, college, and career success. The results revealed that there are key factors significantly impact on the students’ perceptions on academic, emotional, and career development. The author hopes this study will add to the limited existent research on educating the whole child. Also, this study should assist in future policies and practices by providing explorative analyses for students’ attitudes or beliefs for achieving their college and career goals.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/020-886-341-738-646, pop00313 tex.type: [object Object]
Keywords: academic success; career readiness; dept.edl; emotional development; peer-reviewed

A systematic approach to exploring college and career readiness program needs within high-poverty urban public schools - Yavuz, Olcay; Parzych, Jennifer; Generali, Margaret (Education and Urban Society, 2019)
This quantitative correlational study was designed to investigate whether the core and enrichment college readiness program needs within high-poverty urban schools significantly varied with respect to grade level and stakeholder perceptions. Statistically significant differences were discovered in parent, student, and faculty perceptions in core and enrichment programs related to high-poverty urban school needs. The findings provide valuable information about how to design student academic and counseling services strategically and effectively to increase college and career readiness for low-income, urban students. Findings also provide effective strategies for school leaders, educators, and counselors regarding urban school college and career readiness program needs so that resources can be intentionally distributed in areas of greatest importance.
2 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000463178900001, lens.org/043-148-982-388-631, yavuzSystematicApproachExploring2019a tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: accountability; change; dept.csp; dept.edl; peer-reviewed; school improvement; school reform; urban education

Applying SERVQUAL: Using service quality perceptions to improve student satisfaction and program image - Gregory, Jess L. (Journal of Applied Research in Higher Education, 2019)
Purpose: Austerity approaches in higher education require choosing the highest leverage strategies of increasing student satisfaction. Attending to student perceptions of program/service quality (SERVQUAL) is a means to identify areas that have the greatest return on investment. The paper aims to discuss these issues. Design/methodology/approach: This study explores how a program has applied the SERVQUAL model and survey to identify areas for growth. Findings: The survey of 57 students in a cohort-based doctoral program demonstrated the smallest gaps (highest satisfaction) with the domains of empathy (1.33) and responsiveness (1.30) and the lowest with reliability (2.03), tangibles (1.97) and assurance (1.90). Practical implications: While not all of the five dimensions are within the purview of a program to address (some may require funding that is determined at a college or university level), many of the gaps can be addressed by adopting procedures and policies that increase transparency so that students can moderate their expectations and faculty and staff can provide reliable information. Additionally, the use of the SERVQUAL model provided this program with specific, actionable information that could be used to improve the program. Originality/value: The study includes a review of studies that have applied the SERVQUAL model in higher education. The application of SERVQUAL to a cohort-based doctoral program to identify program improvements and steward program image fits into a gap in the extant literature. © 2019, Emerald Publishing Limited.
14 citations (Crossref) [2023-10-31] tex.ids: lens.org/000-458-242-452-814, pop00269 tex.type: [object Object]
Keywords: Market-driven forces in education; SERVQUAL; Service quality; Student satisfaction; dept.edl; peer-reviewed

Editorial: Educational leadership and social justice - Arafeh, Sousan (Journal of Educational Leadership and Policy Studies, 2019)
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found